Volume 2: CFD and VIV 2016
DOI: 10.1115/omae2016-54689
|View full text |Cite
|
Sign up to set email alerts
|

Drag Reduction and VIV Suppression Behaviour of LGS Technology Integral to Drilling Riser Buoyancy Units

Abstract: Drilling risers are regularly deployed in deep water (over 1500 m) with large sections covered in buoyancy modules. The smooth cylindrical shape of these modules can result in significant vortex-induced vibration (VIV) response, causing an overall amplification of drag experienced by the riser. Operations can be suspended due to the total drag adversely affecting top and bottom angles. Although suppression technologies exist to reduce VIV (such as helical strakes or fairings), and therefore redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…AMOG consulting developed an innovative buoyancy module which has a cactus-like cross-sectional body shape called Longitudinally Grooved Suppression (LGS). Water tank experiments have been conducted on the LGS buoyancy modules in large Reynolds Number flow field, and the results showed that the cylinder of a cactus-shaped cross section can reduce VIV responses and drag forces on it simultaneously [5]. In deepwater deployments several risers are often placed together as an array of risers.…”
Section: Introductionmentioning
confidence: 99%
“…AMOG consulting developed an innovative buoyancy module which has a cactus-like cross-sectional body shape called Longitudinally Grooved Suppression (LGS). Water tank experiments have been conducted on the LGS buoyancy modules in large Reynolds Number flow field, and the results showed that the cylinder of a cactus-shaped cross section can reduce VIV responses and drag forces on it simultaneously [5]. In deepwater deployments several risers are often placed together as an array of risers.…”
Section: Introductionmentioning
confidence: 99%